Why do plants respond differently to hydropeaking disturbance? A functional approach. (June 2023) - Baladrón, Alejandro; Bejarano, María Dolores; Boavida, Isabel
Highlights: Plant resistance to hydropeaking was tested using functional trait-based indices. Grasses resisted well hydropeaking flooding and water-level fluctuations. Trees and shrubs may successfully cope with hydropeaking baseflow periods. Forbs were rather vulnerable to all the hydropeaking disturbances. Our indices may help detect suitable species to restore hydropower rivers. Abstract: Hydropeaking, which refers to large and rapid flow fluctuations caused by the turning on or off of hydro-turbines to generate electricity, is a topic of growing interest due to its impact on fluvial ecosystems. To date, most hydropeaking studies have focused on the impact of this hydropower operation mode on invertebrate and fish communities, but little attention has been paid to its impact on riverine communities and how functional traits may make plants resistant to hydropeaking. We determined how a set of 32 plant functional traits are expressed in 14 riverine species, and how such expression affects their capacity to cope with common sources of hydropeaking disturbance (i.e., inundation, water stress, and rapid water fluctuations linked to up-ramping and down-ramping hydropeaking operations). We categorized species as "resistant", "partially-resistant" or "vulnerable" based on the capacity of each trait to confer resistance to hydropeaking disturbances. Two indexes (i.e., "hydropeaking plant species resistance index" (HPPR) and "hydropeaking plant community resistance" index (HPCR)) were developed to rank our species based on their tolerance to hydropeaking and to determine which were the commonest "hydropeaking-resistant" traits within the plant community. Our results evidenced that coincidences in trait expression are common between species with similar growth forms. Grasses were the most resistant to inundation and water fluctuations, whereas trees and shrubs were so to water stress. In general, forbs were rather vulnerable to all the hydropeaking disturbances. The differences observed between the resistance expected and the obtained for several plant species illustrate the importance of our approach to fine-tune the diagnostics on plant species vulnerability to hydropeaking.. We believe this initiative will help river managers to detect suitable species to restore rivers affected by hydropower production.